Alliance With an Unguided Smartphone App: Validation of the Digital Working Alliance Inventory. (September 2022) - Goldberg, Simon B.; Baldwin, Scott A.; Riordan, Kevin M.; Torous, John; Dahl, Cortland J.; Davidson, Richard J.; Hirshberg, Matthew J.
The working alliance may be relevant in unguided smartphone-based interventions, but no validated measure exists. We evaluated the psychometric properties of the six-item Digital Working Alliance Inventory (DWAI) using a cross-sectional survey of meditation app users ( n = 290) and the intervention arm of a randomized trial testing a smartphone-based meditation app ( n = 314). Exploratory factor analysis suggested a single-factor solution which was replicated using longitudinal confirmatory factor analysis. The DWAI showed adequate internal consistency and test–retest reliability. Discriminant validity was supported by a lack of association with social desirability, psychological distress, and preference for a waitlist condition. Convergent validity was supported by positive associations with perceived app effectiveness and preference for an app condition. Supporting predictive validity, DWAI scores positively predicted self-reported and objective app utilization. When assessed at Weeks 3 or 4 of the intervention, but not earlier, DWAI scores predicted pre–post reductions in psychological distress.